Unusual cause of renal failure in infancy: Primary hyperoxaluria - Kanchan Channawar; V S V Prasad (Wolters Kluwer Medknow Publications, 2015)
Background: Primary hyperoxaluria is a rare disease characterized by the excessive production and accumulation of oxalate in the body. Methods: We described the case of an infant with primary hyperoxaluria type who had end-stage renal failure in the second month of life, family history of deaths due to renal disease, renal biopsy showing intense deposition of oxalate crystals 111 the lumen, tubular cells, and kidney interstitium, with secondary glomerular disorder. Conclusions: primary hyperoxaluria type I should be regarded as one of the differential diagnoses of renal failure in the first months of life, especially when no suggestive history of other diseases is present